Peran Karakteristik Personal Auditor Memoderasi Pengaruh Time Budget Presure Terhadap Perilaku Disfungsional Auditor - Sanjaya, I Nyoman Wirada; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p28, 2019)
The purpose of this study is to analyze the role of the characteristics of personal auditors to moderate the effect of budget time on dysfunctional auditors at the Public Accountant Office in the Province of Bali. This research was conducted in nine offices which were still active until 2018 and 70 auditors as samples through the saturated sample method. Data collection was done by distributing questionnaires with 70 respondents that met criteria of testing through the Moderating Regression Analysis (MRA) analysis technique. Based on the results of the analysis, the time budget pressure has a positive influence on the dysfunctional behavior of auditors at the Public Accountant Office in the Province of Bali. The characteristics of personal auditors are able to moderate or strengthen the positive influence of time budget pressure on the dysfunctional behavior of auditors at the Public Accountant Office in the Province of Bali. Keywords : Auditor's Personal Characteristics; Time Budget Presure; Auditor Dysfunctional Behavior.